Aortic Pseudoaneurysm following Ventricular Septal Defect Closure in a Pediatric Patient: A Case Report and Literature Review - Hassan Zamani; Kourosh Vahidshahi; Mohammad Reza Khalilian; Tahmineh Tahouri; Ehsanollah Rahimi-Movaghar (Case Reports in Cardiology)
Aortic pseudoaneurysm, a rare condition characterized by localized transmural disruption and dilatation of the aorta, is very rare in the pediatric population. It is primarily caused by previous cardiovascular procedures such as aortic coarctation repair, aortic valve replacement, and subaortic membrane resection. We present a unique case of aortic pseudoaneurysm following surgery to repair a perimembranous ventricular septal defect in a 19-month-old boy who presented with fever as the sole symptom. The fever started on the 30th day after the surgery, and the patient exhibited abnormal laboratory results, including a white blood cell (WBC) count of 28.3×109/L, neutrophil percentage of 68%, platelet count of 880×109/L, erythrocyte sedimentation rate (ESR) of 200 mm/hour, and 3+ positive C-reactive protein. Echocardiogram revealed a large cystic mass (5×4.8 cm) in the ascending aorta, compressing the superior vena cava. Based on this finding, a diagnosis of aortic pseudoaneurysm was suspected. The diagnosis was confirmed through cardiac computed tomographic angiography, and the patient underwent emergent surgery for the repair of the aortic pseudoaneurysm under deep hypothermia and circulatory arrest. Unfortunately, our patient died shortly after the surgery.